Cognitive Therapy for Children with Intellectual Disabilities: A New Look at Social Adaptation Skills and Interpersonal Relationships - Gulnaz Kulnazarova; Zhamiliya Namazbaeva; Laura Butabayeva; Lazzat Tulepova (Hindawi-Wiley, 2023)
The purpose of the study is to consider the factors influencing the development of the culture of interpersonal relationships and the effectiveness of the influence of cognitive therapy on improving social adaptation skills. The method of cognitive therapy included several types of activities. The first type of activities included group sessions, during which the weaknesses of the interaction and their correction were identified. The second type was conducted in the format of teaching standard models of interaction between people. The third type of activity aimed to teach children to build a dialogue with each other and express their desires and emotions. Classes were held 3 times a week throughout the year. The study was attended by pupils of 5-7 grades of Zhanuya boarding school and special correctional boarding school No. 7 for children with intellectual disabilities. The results of a randomized study demonstrated an increase in the indicators of teamwork skills, self-control, emotional stability, and independent decision-making. The indicators of cheerfulness, openness, sociability, and logical thinking also improved. But the factor of antisocial behavior decreased. All of these indicators directly affect socialization. This strategy can be applied in practice in various specialized boarding schools and schools for children with intellectual disabilities.